Interferon-γ Targets Cancer Cells and Osteoclasts to Prevent Tumor-associated Bone Loss and Bone Metastases - Xu, Zhiqiang (American Society for Biochemistry and Molecular Biology, 2009)
Interferon-γ (IFN-γ) has been shown to enhance anti-tumor immunity and inhibit the formation of bone-resorbing osteoclasts. We evaluated the role of IFN-γ in bone metastases, tumor-associated bone destruction, and hypercalcemia in human T cell lymphotrophic virus type 1-Tax transgenic mice. Compared with Tax(+)IFN-γ(+/+) mice, Tax(+)IFN-γ(-/-) mice developed increased osteolytic bone lesions and soft tissue tumors, as well as increased osteoclast formation and activity. In vivo administration of IFN-γ to tumor-bearing Tax(+)IFN-γ(-/-) mice prevented new tumor development and resulted in decreased bromodeoxyuridine uptake by established tumors. In vitro, IFN-γ directly decreased the viability of Tax(+) tumor cells through inhibition of proliferation, suppression of ERK phosphorylation, and induction of apoptosis and caspase 3 cleavage. IFN-γ also inhibited macrophage colonystimulating factor-mediated proliferation and survival of osteoclast progenitors in vitro. Administration of IFN-γ to C57BL/6 mice decreased Tax(+) tumor growth and prevented tumor-associated bone loss and hypercalcemia. In contrast, IFN-γ treatment failed to protect IFN-γR1(-/-) mice from Tax(+) tumor-induced skeletal complications, despite decreasing tumor growth. These data demonstrate that IFN-γ suppressed tumor-induced bone loss and hypercalcemia in Tax(+) mice by inhibiting both Tax(+) tumor cell growth and host-induced osteolysis. These data suggest a protective role for IFN-γ in patients with bone metastases and hypercalcemia of malignancy.